ANALISIS KESALAHAN BERBAHASA ANAK USIA DINI PADA TATARAN FONOLOGI - Novian Dwi Iswanto (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
Early childhood is in the golden age phase, which is the best time to accept the words they have just heard. In the golden age, the role of parents is very important to improve the vocabulary of children, because at that time early development is more important than later development, when children are influenced by learning and experience. But in the golden age there are often language errors during pronunciation. This study aims to determine the language errors uttered by children aged 2.5 years at the phonological level. The data obtained is when the child is talking and singing, then the stage of collecting data is by listening, taking notes, and recording. The data obtained will be described and classified. The results showed that there were errors in pronouncing words by the children when speaking, such as changing phonemes /r/ to phonemes /l/, or there were words that experienced a reduction in phonemes when spoken. From the analysis, there were 15 errors in phoneme change /r/ to /l/, 14 errors in phoneme change /s/ to /c/, 4 errors of phoneme change /l/ to /w/, 6 errors of phoneme change /k/ to /t/, 3 errors changing the phoneme /r/ to /y/, 2 reducing the phoneme, namely phoneme /l/ in the word "delapan" to "deapan" and phoneme /t/ in the word "istimewa" to "isimewa".